Implementasi Strategi Storytelling Marketing dan Experiental Marketing terhadap Pengembangan Marketing Seniman Kriya Pahat di Bali - Wibawa, Anak Agung Bagus Satria; Luh Putu Mahyuni (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to explore and analyze the implementation of Storytelling Marketing and Experience Marketing strategies in the development of marketing for sculptural handicrafts (kriya pahat) in Bali. Narrative and experiential-based marketing strategies are considered relevant for enhancing emotional engagement and highlighting the cultural values embedded in handcrafted artworks. Employing a qualitative approach with a narrative inquiry method, this research focuses on four key artisan villages: Singapadu, Sukawati, Celuk, and Marga. Data were collected through in-depth interviews, participatory observation, and visual documentation, and were analyzed using narrative analysis techniques. The findings reveal that storytelling centered on cultural philosophy and the creative process fosters strong emotional connections with consumers, while experience marketing via workshops, studio tours, and direct interactions enhances consumer appreciation and loyalty. The integration of both strategies not only expands market reach but also strengthens the cultural identity and competitiveness of Balinese kriya art products in the digital era.